An approach to the reality of Sahara women in Spain - García Vega, Elena; Ahmed-Salem, Fatimetou; Fernández García, Paula; González Menénez, Ana M.ª (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
There are few studies about the feminine emigration in general, and less about Sahara women. The aim of this work is to analyze the reality of this group in Spain, who are emigrants, women and muslims. The sample was made up of 60 women (15-59 years), to which was administered a semi-structured protocol with the following categories of variables: Demographic; work-related; social and gender. We carried out descriptive analysis of the above mentioned variables, showing as singular data the high academic level and their ingrained traditions, barely polluted for the environment. Their formative level and their culture make these women carry out an enormous effort of adaptation to this so different country; this effort many times is not understood by their couples or by their families in the Sahara
Keywords: Women; Emigration; Gender; and Sahara